Female muslim movement in Tatarstan: Historical roots and contemporary realities - Mariam A. Galeeva, Aivaz M. Fazliev, Adelya I. Sattarova, Anvar A. Gafarov, (Opción, 2019)
Origin processes and modern transformations of the women's Muslim movement in Tatarstan are considered in the article. The most important principles of historical knowledge of the theoretical and methodological basis of the research are the scientific character, objectivity and historicism. Authors express the concept that Tatar feminism developed with general modernization of sociocultural way of Russian Muslims on the basis of the ideas of enlightenment, under the influence of Russian acculturation and modernist trends of Muslim East. In conclusion, providing modernist traditions of the past, the modern women's Muslim movement supports the preservation of national, spiritual and religious values of Tatar peop